BROWN DWARFS: MYSTERY AND SHOW - Pavlenko, Ya. V. (Одеські астрономічні публікації, 2017)
Results of the numerical simulation of the spectrum of the brown dwarf candidate Teide 1 discovered by Rebolo et al. (1995) are discussed.